IMPLEMENTASI DWDM PADA ERION TM - Yuniarti, Harumi; Su’udi, Bambang Cholis (Jurnal Teknik Elektro, 2009)
WDM technology has some advantages such as to enhance the network capacity, flexibility,and also has good prospect in the future (at international scale network of the undersea fiberoptics). Based on the advantages in serving the future telecommunication, new techniquecalled DWDM (Dense Wavelength Division Multiplexing) has been applied in instrumentdesigned to serve dense traffic communication. With its product called Ericsson OpticalNetworking (ERIONTM), Ericsson has launched Errion Linier and Erion Flexing Bus. Thisinstrument could transmit 32 channels at same time at operated 0,8 nm channel grid at thirdwindow. Furthermore, it has equipped with traffic protection to solve some failures andmanagement control at operators overview to keep the best performance simultaneously.Keywords: WDM, DWDM, Optical Amplifier, EDFA, Channel Capacity, Digital CrossConnect (DXC).